Terapia fotodinâmica para tratamento de candidíase vulvovaginal em modelo experimental com camundongas - Santi, Maria Eugenia Simões Onofre de (2014)
Vulvovaginal candidiasis is the second most common cause of vaginal infection and it affects 75% of all women at least once during their lifetime. Recurrent vulvovaginal candidiasis represents a challenge to gynecological practice, since some patients frequently experience re-occurrences shortly after antifungal treatment. Antimicrobial photodynamic therapy (PDT) is considered a therapeutically approach in treating fungal infections. The aim of this study was to investigate the efficiency of PDT against yeast infection in animal model. We tested two photosensitizers, methylene blue and PpNetNI combined to light sources. Microbial analysis was performed following treatment and seven days later, and histological examination of vaginal tissue was performed after PDT treatment. PDT inactivated yeast cells and it reduced in 1 log10 for both photosensitizers used and these low-fungal counts were maintained follow 7 days. Histological analysis showed an inhibition of neutrophil influx process in PDT groups and no side effects on tissue was observed. In conclusion, two PDT managements produced antimicrobial effects in this mice infection model and PDT can be considered as potential therapeutic approach to decrease fungal counts in vaginal infection.